Kajian penerapan prinsip konstruksi hijau (green construction) dalam manajemen konstruksi - Jaini, Wahyu Hari Purnomo; Supardi, Sudarman; Watono, Watono (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the application of green construction principles in construction management, with a case study on the construction project of the Governor's Office of West Sulawesi Province. The method used in this research is Importance Performance Analysis (IPA) to assess the performance and importance of green construction attributes, and SWOT analysis to formulate performance improvement strategies. The results showed that the performance level of green construction implementation reached 93%, which indicates that the existing performance needs to be maintained but also requires some improvement in certain aspects with the percentage of conformity level, namely the provision of green open areas 87%, environmentally friendly energy innovation 87% and water management 87%. From the SWOT analysis, internal factors have a value of 2.34 and external factors 2.41, which places this project in quadrant I, signaling the potential for aggressive development. Recommended strategies include strengthening green technology innovation and resource optimization through cooperation with external parties (SO strategy), as well as resource optimization and review of sustainability initiatives (WT strategy). With the implementation of these strategies, it is expected that green construction on this project can significantly contribute to operational efficiency and environmental sustainability. This research also encourages government policies to make green construction a standard in tendering construction projects to support sustainable development in Indonesia.